You need to evaluate the given indefinite integral, hence, you should first reduce the integrand to the most simplified form, such that:

`(x + 3)/(x^2 - 9) = (x + 3)/((x - 3)(x + 3))`

Reducing the duplicate factors, yields:

`(x + 3)/(x^2 - 9) = 1/(x - 3)`

Hence,...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

You need to evaluate the given indefinite integral, hence, you should first reduce the integrand to the most simplified form, such that:

`(x + 3)/(x^2 - 9) = (x + 3)/((x - 3)(x + 3))`

Reducing the duplicate factors, yields:

`(x + 3)/(x^2 - 9) = 1/(x - 3)`

Hence, evaluating the indefinite integral, yields:

`int (x + 3)/(x^2 - 9) dx = int 1/(x - 3) dx`

You should come up with the following substitution, such that:

`x - 3 = t => dx = dt`

Replacing the variable, yields:

`int 1/(x - 3) dx = int 1/t dt`

`int 1/t dt = ln|t| + c`

Replacing back `x - 3` for t yields:

`int 1/(x - 3) dx = ln|x - 3| + c`

**Hence, evaluating the given indefinite integral, yields ****`int (x + 3)/(x^2 - 9) dx = ln|x - 3| + c` .**